Circular design for zero emission architecture and building practice : it is the green way or the highway - Dabaieh, Marwa (Woodhead Publishing series in civil and structural engineering, 2022)
Circular Design for Zero Emission Architecture and Building Practice: It is the Green Way or the Highway presents the main concepts of circular architecture and building design, focusing on emerging trends in zero-emission buildings, particularly zero- and minus- carbon practice. The book is structured around practical design solutions, including research-based passive solutions for extreme climates. It discusses passive and low carbon cooling and heating and natural ventilation, lifecycle assessment and life-cost analysis. The book presents examples and case studies from innovative low-tech to high-tech approaches, covering a wide spectrum of climate zones to show lessons learned and proof of concept. Vulnerable groups of people such as climate refugees are discussed, alongside how vernacular architecture can help introduce practical methods into low-carbon building practices. This book presents theoretical and practical coverage of circular design for zero emission architecture and building in relation to the global challenges of climate change and extreme weather.